STRATEGI PEMBERANTASAN PENYALAHGUNAAN NARKOBA DI KABUPATEN ROKAN HILIR - Nanda Dwika Arrafie; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The distribution of drugs in Rokan Hilir Regency is in an alarming condition. The phenomenon that occurs is (1) District Narcotics Agency (BNK) Rokan Hilir still less in socializing about the dangers of drugs in Rokan Hilir District; (2) in practice in the field, there are still many people who cover up the narcotics circulation so that drug dealers and users are increasing; And (3) the difficulty of District Narcotics Board (BNK) Rokan Hilir in suppressing the number of drugs Rokan Hilir DistrictThe purpose of the study: (1) to know the strategy of eradication of drug abuse in Rokan Hilir Regency; (2) to know the factors that influence eradication of drug abuse in Rokan Hilir Regency. Informants of this study were taken from the Police Section Eradication Drugs, General Kaur Narcotics Agency Rokan Hilir District, Section Members of the Rokan Hilir District Narcotics Board and Customs Members Rokan Hilir District. Population used as informant because this research use qualitative research. Types and data sources use primary data, ie data obtained directly from respondents and secondary data, ie data obtained through reports, books and records. Data collection techniques use observation, interview and documentation. Data analysis techniques by data collection, data reduction, data presentation, and draw conclusions.Based on the result of research, that strategy of eradication of drug abuse in Rokan Hilir Regency is done by using Strenghts indicator (strength), Weakness (Opportunity), Opportunities (Opportunity), Threats (Threats). Factors influencing drug eradication in Rokan Hilir Regency consist of: (1) lack of information; (2) Facilities and Infrastructure; And (3) Participation; (3) Motivation.Keywords: Strategy, Eradication of Drug Abuse